2017
DOI: 10.1371/journal.pcbi.1005440
|View full text |Cite
|
Sign up to set email alerts
|

Increased decision thresholds enhance information gathering performance in juvenile Obsessive-Compulsive Disorder (OCD)

Abstract: Patients with obsessive-compulsive disorder (OCD) can be described as cautious and hesitant, manifesting an excessive indecisiveness that hinders efficient decision making. However, excess caution in decision making may also lead to better performance in specific situations where the cost of extended deliberation is small. We compared 16 juvenile OCD patients with 16 matched healthy controls whilst they performed a sequential information gathering task under different external cost conditions. We found that pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
159
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(175 citation statements)
references
References 73 publications
16
159
0
Order By: Relevance
“…We used the total scores as a dependent variable in a fivefold crossvalidated regression (cf. 84,97). To assess whether apathy was more closely linked to dmPFC or VS activation, we used the activation in the given ROI (using mean activation at P < 0.05 FWE ROI, same as in previous analyses), including both effort and reward prediction error signals at the time of outcome.…”
Section: Methodsmentioning
confidence: 99%
“…We used the total scores as a dependent variable in a fivefold crossvalidated regression (cf. 84,97). To assess whether apathy was more closely linked to dmPFC or VS activation, we used the activation in the given ROI (using mean activation at P < 0.05 FWE ROI, same as in previous analyses), including both effort and reward prediction error signals at the time of outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings might provide a benchmark to uncover social value computation aberrations in psychiatric disorders. Some psychiatric disorders can be characterized by biases in information sampling, such as insufficient information gathering in addiction 30 , asymmetric weighting of negative evidence in depression 31 , and impaired information sampling cost signals associated with compulsivity 32,33 . Importantly, specific impairments in the ability to model the moral character of others or to respond to social signals are central to a range of psychiatric disorders, including borderline personality disorder and autism spectrum disorder 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Such behaviour is found in patients (Fear and Healy, 1997;Moutoussis et al, 2011;e.g., Dudley et al, 2016), but is also a feature of prodromal states (Rausch et al, 2016) and first-degree relatives (Van Dael et al, 2006). This contrasts with patients diagnosed as having obsessive-compulsive disorder (OCD) who tend to gather more information (Volans, 1976;Fear and Healy, 1997;Pélissier and O'Connor, 2002;Voon et al, 2016;Hauser et al, 2017cHauser et al, , 2017b, although not ubiquitously so (Chamberlain et al, 2007;Jacobsen et al, 2012;Grassi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The neurocognitive control mechanisms that drive these effects is unknown. Using Bayesian computational modelling, we recently showed that one key contributor is a decision urgency signal that promotes timely decisions (Hauser et al, 2017c(Hauser et al, , 2017b. The neural processes that modulate such urgency signals in sequential information gathering remain unknown.…”
Section: Introductionmentioning
confidence: 99%